USM BRINGS AIDILFITRI CHEER TO YOUNG PATIENTS IN PENANG GH - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, July 2015 Universiti Sains Malaysia (USM) will continue to help those in need by organising more community engagement programmes as a way of showing care and concern to the surrounding communities as well as bringing festive cheer to them.